WHY MEDIA SLANT? Media coverage of mergers and acquisitions in China. Issue 1 (31st December 2022) - Wu, Chao; Yang, Shuai
Abstract: Using a text analysis of Chinese newspaper articles covering 1321 proposed mergers during 2008–2018, this study proposes attribution theory to examine how the media is susceptible to stereotype bias. Evidence reveals that the media pays considerable attention to and exhibits favourable sentiments toward overseas-experienced acquirers, which is found only in non-state-owned enterprises. Further analyses on the amplifying effect of stereotype bias show that the media slant more positively on large-scale overseas experiences. Results indicate that the media is biased, referring to impression migration from merger and acquisition experience.